Electrokinetic Energy Conversion in Self‐Assembled 2D Nanofluidic Channels with Janus Nanobuilding Blocks. Issue 23 (11th April 2017) - Cheng, Hongfei; Zhou, Yi; Feng, Yaping; Geng, Wenxiao; Liu, Qinfu; Guo, Wei; Jiang, Lei
Abstract : Inspired by the microstructure of nacre, material design, and large‐scale integration of artificial nanofluidic devices step into a completely new stage, termed 2D nanofluidics, in which mass and charge transportation are confined in the interstitial space between reconstructed 2D nanomaterials. However, all the existing 2D nanofluidic systems are reconstituted from homogeneous nanobuilding blocks. Herein, this paper reports the bottom‐up construction of 2D nanofluidic materials with kaolinite‐based Janus nanobuilding blocks, and demonstrates two types of electrokinetic energy conversion through the network of 2D nanochannels. Being different from previous 2D nanofluidic systems, two distinct types of sub‐nanometer‐ and nanometer‐wide fluidic channels of about 6.8 and 13.8 Å are identified in the reconstructed kaolinite membranes (RKM), showing prominent surface‐governed ion transport behaviors and nearly perfect cation‐selectivity. The RKMs exhibit superior capability in osmotic and hydraulic energy conversion, compared to graphene‐based membranes. The mineral‐based 2D nanofluidic system opens up a new avenue to self‐assemble asymmetric 2D nanomaterials for energy, environmental, and healthcare applications. Abstract : Self‐assembled Janus nanokaolinite, forming a network of cascading 2D nanofluidic channels is reported. Two distinct types of sub‐nanometer‐ and nanometer‐scale fluidic channels of about 6.8 and 13.8 Å endow the membrane channels with nearly perfect cation selectivity. Three types of electrokinetic ionic‐transport behaviors are investigated. The mineral‐based 2D layered material is highly competent for nanofluidic energy conversion.